3x+7+5x-3=90

Simple and best practice solution for 3x+7+5x-3=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7+5x-3=90 equation:


Simplifying
3x + 7 + 5x + -3 = 90

Reorder the terms:
7 + -3 + 3x + 5x = 90

Combine like terms: 7 + -3 = 4
4 + 3x + 5x = 90

Combine like terms: 3x + 5x = 8x
4 + 8x = 90

Solving
4 + 8x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 8x = 90 + -4

Combine like terms: 4 + -4 = 0
0 + 8x = 90 + -4
8x = 90 + -4

Combine like terms: 90 + -4 = 86
8x = 86

Divide each side by '8'.
x = 10.75

Simplifying
x = 10.75

See similar equations:

| 64y^2-36=0 | | 3x+7+5x-3=180 | | 2x+14=4x-6 | | 0=60.5+13.3t-4.9t^2 | | x^2+10x+8y+41=0 | | 19x+6=32+4x | | 17=37+4 | | 10t^2=5 | | 5c+24=4 | | x+2x+17=80 | | (9x^2)-18x+9=47 | | 13+3p=9 | | x-2+x+x+3=34 | | (49x^2)+14x+1=9 | | h+h+14=306 | | t+2t=5+7 | | -16t^2+18=10 | | (16x^2)+2x-3=0 | | x-1+x+x+2=37 | | -2b+4=3b | | Qs=-20+3 | | (2x^2)+12x=0 | | y=(x-1.2) | | 5.5x=102.50 | | 2h+18=266 | | (w-2)+w+(w+3)=40 | | (x-2)3=64 | | 2x^2+36x-176=0 | | 6x^2-2x^2=2y^2 | | 2y+17=-4y-25 | | 8x+3x=180 | | -196x^2+676=0 |

Equations solver categories